Model-Model Desain Pembelajaran pada Kurikulum 2013 SD Rawa Bokor - Herlina Efendi; Ina Magdalena; Ismiatun Nazifah (RC-INSTITUT, 2021)
This research is a very important activity in knowing how to teach properly, in this case we as PGSD students conduct research at SD Rawa Bokor school to fulfill assignments in the form of observation of learning in particular in class. With this research, it is hoped that we can find out how a teacher teaches, then we as prospective teachers can certainly choose which ones are good and which are not good to be taught to, urid when we are teaching later. The aim is to find out the method of a teacher in delivering, to know the child's listening ability to some of the methods presented, and to find out which method the child is interested in when listening. This research uses qualitative research using the interview method. Interviews were conducted offline by visiting resource persons, namely the SD Rawa Bokor class teacher. The results of the interview show that SD Rawa Bokor has used the 2013 curriculum as learning.